Humoral immune responses to inactivated COVID-19 vaccine up to 1 year in children with chronic hepatitis B infection - Zhou, Yingzhi; Chen, Zhiwei; He, Yi; Peng, Xiaorong; Chang, Yunan; Tan, Aoxue; Li, Hu; Cai, Dachuan; Hu, Peng; Chen, Min; Peng, Mingli; Xu, Hongmei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Inactivated SARS-CoV-2 vaccination has recently been approved for children aged 3-17 years in China. However, data on long-term humoral responses to inactivated vaccines in children with chronic hepatitis B (CHB) are still limited. Methods In this prospective observational study, CHB children after primary inactivated SARS-CoV-2 vaccines were recruited consecutively and followed up for 1 year. CHB adults from another cohort study (NCT05007665) were used as a control. The receptor-binding domain IgG antibody (anti-RBD-IgG), neutralizing antibody (NAb), neutralization against Omicron (BA2.12.1, BA.4 and BA.5), and memory B -cell (MBC) responses were evaluated. Results Overall, 115 CHB children and 351 CHB adults were included in this analysis. The antibody titers decreased over the first 180 days and then plateaued up to 1 year in CHB children. However, lower and faster declines in antibody responses were observed in CHB adults. Interestingly, the seroprevalence of antibodies was still high after over 8 months in CHB children (anti-RBD-IgG [90%] and NAbs [83%]). However, neutralization against Omicron subvariants was significantly reduced in CHB children (-3.68-fold to -8.60-fold). Notably, neutralization against the BA.5 subvariant was obviously diminished in CHB children compared with adults. Moreover, CHB children had similar RBD-specific MBCs but higher RBD-specific atypical MBCs compared with adults. Conclusion Inactivated vaccination could elicit more robust and durable antibody responses to the wild-type SARS-CoV-2 strain in CHB children than in CHB adults but showed inferior responses to Omicron subvariants (especially to the BA.5 strain). Hence, new Omicron-related or all-in-one vaccines are needed immediately for CHB children.